Kebahagiaan Petani Dusun Tegal Bedug, Kabupaten Indramayu - Soetikno, Naomi; Yesia, Mitta; Carlos Youpiter, Yohannes; Lyana, Hanny; Dwita Aprilia, Sarah; Syahputra Harahap, Rizky; Maurilla Santoso, Naomi (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2023)
Happiness is a form of feeling that every individual expects. The existence of happiness experienced by individuals can impact one's performance and enthusiasm for life. In the village of Tegal Bedug, Indramayu district, the economic condition of the residents as farmers affects the happiness that they feel in their lives. The purpose of this study was to describe the happiness of the residents of Tegal Bedug village who work as farmers. The research method used is a mixed method descriptive design. By using the Oxford Happiness Questionnaire, it was found that from 37 farmer participants the level of happiness of the residents of Tegal Bedug village is average. Happiness in Tegal Bedug village is a mix of interaction between its social environment and individual attributes. The main factors that make them happy are health, interaction with family members, and achieving targets. Some who rate their happiness low give negative evaluations of themselves, their environment, and their future. Recognizing the interaction between individual attributes and social and environmental factors is crucial to maximizing the outcome of the intervention and implications in sociological and psychological studies, specifically for farmers in rural areas.